(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Speech disorders in children are a significant concern in the field of speech therapy and special education. This thesis explores the rehabilitation methods for children with speech disorders, focusing on the scientific basis, practical approaches, and outcomes of intervention programs. The study highlights the importance of early diagnosis and individualized therapy plans to improve communication skills and social integration. Key findings suggest that a combination of traditional and innovative methods yields the best results in speech rehabilitation. The thesis concludes with recommendations for further research and practical applications in the field.